The Effect of Using Virtual Reality on Labor Pain in Primipara at Puskesmas PONED New Village - Satria, Epi; Niawati, Lis (JURNAL IBU DAN ANAK, 2022)
Pain is part of the birth process, approximately 90% of deliveries are accompanied by pain and 7-14% are not accompanied by pain. Virtual Reality (VR) is a non-pharmacological method of pain relief. The purpose of this study was to determine the effect of the use of virtual reality on labor pain in primiparas at the PONED Health Center in Baru Village. This type of research is experimental research and the research design is pre-experimental pre-test and post-test using the one group pre-test post-test design. The research population was Primipara Maternity Mothers with a sample of 6 respondents who were given Virtual Reality, using a non-probability technique with total sampling, namely the sampling method was carried out by taking all members of the population as respondents or samples. The results of the study obtained Value = 0.001 <0.05, this shows that there is an effect of using virtual reality on labor pain in birthing mothers. Suggestions for future researchers can be done by entering the video that will be displayed directly into the VR tool so that it is no longer connected to a cellphone.